(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
This contribution is meant to analyze the the techno-cognitive assemblages that streaming platforms are part of, and how streaming platforms create the conditions for a “physiognomy” of listening habits under the premises created by the automatic distributed listening on which their functioning relies. Considering the genealogy of digital music formats (Sterne, 2012), interrogating the retromaniac (Reynolds, 2011) re-mediations taking place within streaming platforms, looking at the shifts and clashes generated by automation (Reynolds, 2011; Burrows and O’Sullivan, 2018), and using noise theory and noise philosophy (Attali, 1985; Brassier, 2011; Malaspina, 2018; Mattin, 2022), this text will attempt to elucidate different non-sonic constraints that inform and shape the way we engage with listening routines, while also analyzing streaming-reliant listening habits through the lens of noise and noise philosophy. If noise is the disruption that becomes prerequisite for a selfless subject (Brassier, 2009), could we argue that noise-reliant algorithmic systems, based on the objectivity of machinic listeners, organize the chaos of desiring subjects by creating the illusion of a unique self, but in reality becoming the ultimate breeding ground for nemocentric (Metzinger, 2004) production of subjectivities? These subjectivities can be considered nemocentric (namely: without a center) because distributed across the cognitive assemblages of platform capitalism, dematerialized and scattered. If noise has been subsumed under the “masking” (Sterne, 2012) premises of platform capitalism, how do nemocentric subjects operate under the prescriptive logics of the very capitalist structures that produced them?